Robot Kits in Primary Informatics Education - What Should Future Teachers Know? - Mikova, Karolina; Budinska, Lucia (2021 19th International Conference on Information Technology Based Higher Education and Training (ITHET), 2021)
In the last years, many robot kits for children were introduced. They can be used as an introduction to programming when pupils can learn many computing concepts - as a part of informatics or in STEAM subjects. But not many of the kits are suitable for education, some of them are not age-appropriate others can be used only for small tasks only or have a steep learning curve. In this paper, an analysis of 8 robot kits was performed. All of the kits can be used with pupils from 3 to 12 years old. In the analysis, the main focus was on interactivity (which is specific to robotic programming compared to basic text or visual programming languages) and programming concepts (what can pupils learn from programming) and a robot movement. The robot movement is an area in between the programming and interactivity because when children program the movement of a robot, they need to think about its interaction with the environment it is in. This analysis was carried out to help create the content of the Educational Robotics course at the university for students of computer science teaching,